2022
DOI: 10.1093/icesjms/fsac164
|View full text |Cite
|
Sign up to set email alerts
|

An overview on elasmobranch release as a bycatch mitigation strategy

Abstract: Sharks and rays are among the most threatened vertebrates, mostly due to commercial fisheries. Data on incidental capture is sparse, but it is estimated that about 50% of reported global catches of elasmobranchs are from bycatch. Elasmobranchs are captured in a variety of fishing gear throughout the world. One promising strategy to minimize incidental catches is the release of live sharks and rays. However, so far, no critical analysis had been carried out to assess the importance of release as a measure to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…While avoidance of capture would be ideal to conserve threatened bycatch species (Milner‐Gulland et al, 2018), it would be challenging here due to the relatively low selectivity of gear and shared habitats with target species. Release can be an effective and low‐cost conservation measure in tropical, mixed species fisheries, especially when measures like spatial closures or gear modifications are not feasible (Gupta et al, 2020; Wosnick et al, 2022). Although poorly studied, some studies have noted moderate to high survival rates post‐capture for different rhino ray species (Fennessy, 1994; Prado et al, 2021; Stobutzki et al, 2002); high survival has also been observed by fishers in our study site.…”
Section: Discussionmentioning
confidence: 99%
“…While avoidance of capture would be ideal to conserve threatened bycatch species (Milner‐Gulland et al, 2018), it would be challenging here due to the relatively low selectivity of gear and shared habitats with target species. Release can be an effective and low‐cost conservation measure in tropical, mixed species fisheries, especially when measures like spatial closures or gear modifications are not feasible (Gupta et al, 2020; Wosnick et al, 2022). Although poorly studied, some studies have noted moderate to high survival rates post‐capture for different rhino ray species (Fennessy, 1994; Prado et al, 2021; Stobutzki et al, 2002); high survival has also been observed by fishers in our study site.…”
Section: Discussionmentioning
confidence: 99%
“…Catch‐and‐release guidelines should be developed in collaboration with specialists and rely on participation by recreational fishers to draw on their substantial knowledge regarding capture techniques, injuries observed, mortality incidents, and other insights (Brownscombe et al., 2017). Guidelines should prioritize simplicity, clarity, and visual aids to effectively convey best practices and discourage harmful methods (Wosnick et al., 2023). Moreover, an identification guide for guitarfishes in the Pseudobatos genus is needed, in straightforward language with easily recognizable features (Leite, 2022).…”
Section: Discussionmentioning
confidence: 99%